Phage display selection of peptide inhibitors of FVIIa and their functional characterisation - Roets, Catharina Elizabeth (University of the Free State, 2002)
The importance of FVlla and the FVlla/TF complex for the initiation of not only hemostasis but also thrombosis is now generally accepted. It was shown that the blockade of coagulation at the level of FVlla provided full anti thrombotic protection without abnormal bleeding (Harker et aI, 1996), therefore FVlla is a suitable candidate for the development of novel antithrombotics. We selected inhibitors to FVlla using the technique of phage display. A repeated selection of phages from a cyclic heptapeptide and a linear 12-mere phage display library resulted in the enrichment of phages that bind to human FVlla. We selected twelve colonies (6 from each library) that showed the strongest binding to FVlla. The colonies from the cyclic 7-mere library showed a higher affinity binding for FVlla than the colonies from the linear 12- mere library. TF also prevents the binding of one of the cyclic colonies to FVlla. This colony as well as one colony from the linear library showed lengthening of the prothrombin time (PT) as well as the thrombin time (TT) in a dose-dependent manner. A cyclic heptapeptide was synthesised with the corresponding sequence as the sequence displayed on the cyclic 7-mere colony. The peptide showed lengthening of the PT and TT in a dose-dependent manner with a more pronounced effect on the PT than the TI. We also studied the effect of this peptide on platelet adhesion on human vascular endothelial cell matrix, collagen and TF under both venous and arterial shear stresses. The peptide inhibits platelet adhesion to HMEC-1 under both shear stresses. The effect on arterial shear is however more pronounced. It does not inhibit platelet adhesion to collagen, but has a dose-dependent inhibitory effect on platelet adhesion TF at arterial shear. Kinetic analysis of the peptide showed that this peptide is a competitive inhibitor of FVlla by altering the Km-values but not the Vmax-values. The Lineweaver-Burk plot also indicates a competitive inhibition, because the slope of the graphs increased with increasing inhibitor concentrations. The Ki-value was determined at 0.1232 mM. In summary, this peptide inhibits thrombus formation by preventing FVlla from binding to TF and therefore preventing the activation of FX by the FVlla/TF complex. This study suggests that inhibitors to FVlla provide a novel therapeutic approach to prevent thrombosis.

Dit word nou algemeen aanvaar dat faktor Vila en die faktor VllalWeefselfaktor (FVlla/WF) kompleks nie alleen 'n baie belangrike rol in hemostase speel nie, maar ook in trombose. Deur die stollingskaskade op die vlak van FVlla te blokkeer, lei tot volledige inhibisie van trombose sonder die moontlikheid van 'n bloedingsneiging (Harker et al, 1996). FVlla is dus 'n geskikte kandidaat waarteen nuwe anti-trombotiese middels ontwikkel kan word. Die tegnologie van peptiedblootlegging op fage is gebruik om inhibitore teen FVlla te selekteer. Herhaalde seleksie van fage vanaf 'n sikliese heptapeptied faag biblioteek asook 'n lineêre 12-aminosuur faag biblioteek het gelei tot die vermeerdering van fage wat spesifiek bind aan FVIIa. Ons het twaalf kolonies wat sterk aan FVlla bind geselekteer (6 van elke biblioteek). Die sikliese kolonies het met hoër affiniteit aan FVlla gebind. Ons het ook gevind dat WF di~ binding van een van die sikliese kolonies aan FVlla verhoed. Hierdie kolonie asook een van die lineêre biblioteek het dosisafhanklike verlenging getoon met die protrombien tyd (PT) en die trombien tyd (TT). Ons het 'n sikliese hepta-peptied identies aan die peptied wat blootgelê word op die sikliese faag kolonie, laat sintetiseer. Die peptied verleng die PT en TT. Die effek was dosis-afhanklik en was meer uitgesproke in die PT as in die TT. Ons het ook die effek van die peptied op plaatjie adhesie gaan ondersoek. Ons het verskillende oppervlaktes gebruik, nl. menslike vaskulêre endoteelsel-matriks, kollageen en WF. Daar is van beide veneuse en arteriële skuifkragte gebruik gemaak. Die peptied inhibeer plaatjie adhesie aan die menslike vaskulêre endoteel. Die effek was meer uitgesproke in die geval van arteriële vloei. Die peptied het egter geen effek getoon op plaatjieadhesie aan kollageen nie. Daar was wel 'n dosis-afhanklike effek op plaatjie adhesie aan WF in arteriële vloei. Ons het ook kinetiese analises van die peptied gedoen. Die peptied is 'n kompeterende inhibeerder van FVlla. Die Km-waardes varieer met verskillende peptiedkonsentrasies, maar nie die Vmaks-waardes nie. Die Ki waarde is 0.1232 mM. Ter opsomming kan ons sê dat hierdie peptied trombusvorming inhibeer deur te verhoed dat FVlla aan WF bind en daardeur die aktivering van faktor X deur die FVlla/WF kompleks verhoed. Hierdie studie dui daarop dat die ontwikkeling van inhibitore teen FVlla In nuwe benadering is om trombose te voorkom.
Thesis (Ph.D. (Haematology and Cell Biology))--University of the Free State, 2002
Keywords: Blood coagulation factors; Peptides